∫ 0 1 1 + x 3 1 − x 3 d x
If the above integral can be expressed in the form
− a + d b π c + g f ln 2
where a , b , c , d , f , g are positive integers and g cd ( b , d ) = g cd ( f , g ) = 1 , find a + b + c + d + f + g .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
how to simplify x 2 − x + 1 3 \dx ?
Log in to reply
x 2 − x + 1 3 = ( x − 2 1 ) 2 + 4 3 3 And then use : ∫ x 2 + a 2 d x = a 1 ( tan − 1 a x ) and apply appropriate limits.
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 1 ( 1 − x 3 1 + x 3 ) d x = ∫ 0 1 ( − 1 + 1 + x 3 2 ) d x S = ∫ 0 1 ( 1 + x 3 1 ) d x = 3 1 ∫ 0 1 ( 1 + x 1 + 2 1 ( x 2 − x + 1 − 2 x + 1 + x 2 − x + 1 3 ) ) d x See this for Integration using Partial fractions = 3 1 ( ln ( 1 + x ) − 2 1 ( ln ( x 2 − x + 1 ) + 2 3 ( tan − 1 ( 3 2 x − 1 ) ) ) ∣ 0 1 = 3 1 ln 2 + 9 π 3 Hence, I = − 1 + 2 S = − 1 + 3 2 ln 2 + 9 2 π 3 ∴ 1 + 2 + 3 + 9 + 2 + 3 = 2 0